Determining the relationship between the body image of adolescent girls and their academic achievement, social involvement and sport participation : a pilot study - Mostert, Petronella Louisa (Rhodes University, Faculty of Education, Department of Education, 1995)
Ever since the earliest times much emphasis has been placed on the physical appearance of women. Particularly in western cultures idealized images of perfection are constantly promoted and the message that comes across in various media outlets is that a woman ought to have a 'perfect' appearance in order to be competent and desirable. This puts a great deal of stress on women and particularly on adolescent girls who are going through a phase of increased sensitivity about their appearance. The literature suggests that people, and women in particular, are fundamentally affected by the way they view their bodies. The body image furthermore has a strong relationship with the self concept, which affects other areas of a person's life such as her academic achievement and her social 'life. Against this background an attempt was made in this study to determine the relationship between the body image of adolescent girls and their academic achievement, their sport participation and their social involvement. The subjects were 180 girls drawn from two rural secondary schools. The survey involved the completion of two questionnaires, namely an adapted form of the Physical Self Subscale of the Tenessee Self Concept Scale (used to determine a score for body image) and a questionnaire on social involvement and sport participation, which was drawn up by the researcher. Biographic data as well as academic scores were gathered from school records. Data was analysed statistically by means of the BMDP Software Version 1990: programme (Sun Unix). Pearson's chi square tests of independence, as well as a one-way analysis of variance with co-variate were carried out. The results reveal that the body image and academic achievement of this group of girls are not significantly correlated. There are, however, significant correlations between the body image and social involvement of these girls, between their body image and sport participation, as well as between their social involvement and sport participation. iv These findings have important implications for"'e"ducation and consideration is given to addressing these issues in schools.
Keywords: Body image in adolescence; Personality and academic achievement; Social interaction in adolescence; Self-perception in adolescence; Teenage girls -- Psychology; Academic achievement